SUSTAINABILITY IN BARISTA SKILLS; MONITORING AND EVALUATION FROM BARISTA’S KNOWLEDGE IN SPECIALTY COFFEE AT THE COFFEE LAB DUBAI 2021 - Kurniawan Arif Maspul (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2022)
Today’s number of coffee shops is inseparable from the third-wave in the coffee supply chain, especially the recent growth of specialty coffee. Sustainability is the main goal for all sectors, including the standardised solder of the supply chain in the coffee shop. Numerous Baristas do not yet understand the importance of sustainability in their coffee bar and management realm. To raise sustainability so that it is aligned with skills and behaviour in ethical business, it is essential to apply sustainable education in the Barista concept of thinking, understand their philosophy as coffee brewers and connect all stakeholders in the coffee supply chain to consumers who need this information. This issue is a sustainability challenge for Barista to be strengthened by knowledge. The continuation of a blended curriculum for professional coffee through the coffee skills program of the Specialty Coffee Association with the “Introduction to Coffee” module will eliminate the barrier of deficiencies for Baristas. It makes Barista’s existence an agent of change in bringing sustainability to the coffee supply chain. This curriculum was delivered along with additional coaching, assessment, and interview at the end of the activity to measure material for Barista knowledge. The current object for this study was Barista at The Coffee Lab Dubai, the United Arab Emirates.